Reconsidering the context in the relationship between material deprivation and self-rated health among older people in Italy - Roberta Misuraca; Maria Carella (PLoS ONE, 2026)
Both personal characteristics and contextual factors shape an individual’s perception of their health. This is especially true among older people. Micro and macro data from the 2018 Italian Multipurpose Survey on Households and a two-step model have been used here to investigate the extent to which macro-level factors (at the regional level) explain variations in the nexus between material deprivation and self-rated health among older individuals in Italy, after considering micro characteristics. Our findings show that contextual variables, such as per capita GDP, tertiary education rates, and the availability of care home facilities, not only significantly moderate the effect of material deprivation on SRH but may paradoxically intensify its negative effects in wealthier or better-resourced regions. This counterintuitive pattern suggests that mechanisms of relative deprivation and social comparison are particularly salient in later life. These findings highlight the importance of context-sensitive, inclusive policy interventions that address both structural-economic disparities and the psychosocial realities of inequality to improve health outcomes for older populations.